2013
DOI: 10.4025/actasciagron.v35i1.15516
|View full text |Cite
|
Sign up to set email alerts
|

Cycle, canopy architecture and yield of common bean genotypes (Phaseolus vulgaris) in Santa Catarina State

Abstract: ABSTRACT. The objective of this study was to identify the phenotypic and genotypic correlations between the plant cycle and plant habit and the effect on yield in landrace bean genotypes. The experiment was conducted in Joaçaba and Lages, Santa Catarina State for the 2008/2009 crop using 26 bean genotypes: 22 landrace and 4 commercial genotypes obtained from the UDESC. We evaluated the number of days from emergence to flowering, number of days from flowering to physiological maturity and number of days from em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
5

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
3
6
0
5
Order By: Relevance
“…In Santa Maria, three land cultivars (Amendoim, Mourinho, and Carioca Vermelho) surpassed the four control cultivars with respect to the insertion of the first pod. Similarly, Zilio et al (2013) observed that the insertion of the first pod, which was evaluated for 22 common bean land cultivars, varied by growing location, and the ranking of the cultivars changed when they were evaluated in another environment in the Santa Catarina state. The cultivars Mourinho and Carioca Vermelho had a higher insertion of the first pod in both growing locations and are therefore promising for breeding programs.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In Santa Maria, three land cultivars (Amendoim, Mourinho, and Carioca Vermelho) surpassed the four control cultivars with respect to the insertion of the first pod. Similarly, Zilio et al (2013) observed that the insertion of the first pod, which was evaluated for 22 common bean land cultivars, varied by growing location, and the ranking of the cultivars changed when they were evaluated in another environment in the Santa Catarina state. The cultivars Mourinho and Carioca Vermelho had a higher insertion of the first pod in both growing locations and are therefore promising for breeding programs.…”
Section: Resultsmentioning
confidence: 94%
“…In Santa Maria, the land cultivars Azulão, Guabiju, Cavalo, Cavalo Rajado, Cavalo Rio Pardo, and Grosso Santa Maria and the control cultivar Guapo Brilhante had early cycle. Previous studies have shown that the cycle of common bean land cultivars changes depending on year (RIBEIRO et al, 2008a) and growing location (ZILIO et al, 2013). Thus, identification of common bean land cultivars with early cycle, defined by Zimmermann and Teixeira (1996) as those cultivars with approximately 70 days from emergence to maturation, independent of growing environment, is of great importance to breeding programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erect cultivars facilitate cultural practices, enable mechanized harvesting, and ensure higher quality grains (Mendes et al, 2009;Silva et al, 2009;Zilio et al, 2013). Unfortunately, the evaluation of plant architecture by visual grade (Collichio et al, 1997) is more propitious to error, as it requires the evaluators to have experi-ence and training.…”
Section: Resultsmentioning
confidence: 99%
“…La precocidad de Verdín y SEN-56, se ha documentado en estudios de evaluación realizados en el estado de Veracruz (Tosquy et al, 2014), la cual es importante para evitar la sequía terminal, ya que les permite a las plantas de frijol completar su ciclo y escapar a la sequía antes de que se presenten problemas críticos por falta de humedad (Acosta-Díaz et al, 2004;AcostaGallegos y Kelly, 2012). A su vez, los genotipos con mayor número de días en llegar a madurez en condiciones limitadas de humedad, muestran menor productividad (Zilio et al, 2013). OI= ciclo otoño-invierno; PV= ciclo primavera-verano; ** = diferencia altamente significativa; * = genotipos estadísticamente superiores, según la diferencia mínima significativa (0.05).…”
Section: Madurez Fisiológica Y Rendimiento De Granounclassified